The mobile-only population in Portugal and its impact in a dual frame telephone survey - Vicente, P. (2017)
In 2007 the percentage of mobile-only households in Portugal reached 36%; this is one of the highest levels in EU27 countries according to the EU E-Communications Households Survey. To assess the extent and nature of the potential bias in fixed phone surveys created by the absence of mobile-only households, a dual frame survey was conducted in which both fixed phones and mobile phones were used to collect data. There are significant differences between fixed phone respondents and mobile-only respondents in several demographic variables; however, we find that merging the fixed phone and the mobile-only sample produces general population estimates on substantive variables that are not significantly different from those obtained with the fixed phone sample alone.